The Common Assessment Framework in practice: a performance enhancing tool or a box-ticking formality? Evidence from the Greek public sector - Rammata, Maria; Antonopoulos, Eleftherios; Kopsidas, Odysseas (International Conference on Business and Economics - Hellenic Open University, 2023)
The Common Assessment Framework (CAF) is recognized as a tool for improving the performance of public bodies based on the principles of Total Quality Management (TQM) (e.g. measurement, Key Performance Indicators (KPI), assessment, standardized procedures, etc.). Organisational self-assessment constitutes a key element in CAF application, and it enhances the integration of essential management principles in the every-day working routine of public services. During the last decade, the Greek public sector has been placed under external scrutiny and domestic pressure to overhaul its structures, improve its overall performance, and upgrade its positive impact on the socioeconomic development. In light of these challenges, it is important to discuss if CAF and under what conditions can effectively contribute to introduce quality improvements in the performance of the Greek public sector. Hence, this paper examines and discusses critically CAF implementation in specific Greek public services, e.g. a general hospital A&E department, a recruiting office, and a directorate of a central government ministry. The existing literature on CAF applications is reviewed and fieldwork interviews are used to provide empirical testing in three of the CAF applications. Findings demonstrate its limited impact so far, the piecemeal approach followed in many cases, and perceived weaknesses of abstract, catch-all sub-criteria designed to cover all types of services. However, in the majority of cases studied, CAF has been the first application of quality management principles and thus introduced performance measurement tools and improvement action plans. Key recommendations include the need to provide incentives to authorities for encouraging CAF applications and promote a standardized approach, which could pave the way for quality accreditation of the organisations involved.